Ultrasound examination at term for predicting the outcome of delivery in women with a previous cesarean section. (1st December 2016) - Comas, Montse; Cochs, Belén; Martí, Laia; Ruiz, Raquel; Maireles, Sònia; Costa, Jordi; Canet, Yolanda
Abstract: Objective : To evaluate if ultrasound variables at term are associated with the mode of delivery in women with previous cesarean section (PCS) . Methods : This was a prospective study of singleton pregnant women who planned a trial of vaginal birth after cesarean delivery. Cervical length, posterior cervical angle, head–perineum distance, and estimated fetal weight were measured at 37–39 weeks of gestation. Results : One hundred forty-four pregnancies were examined and vaginal delivery was achieved in 98 women (73%). Logistic regression analysis identified cervical length, head–perineum distance, age, previous vaginal delivery, previous cesarean for dystocia, and Bishop score as predictors of vaginal delivery. Combining ultrasound and clinical parameters, two models for risk scoring that differ in the variable Bishop score or cervical length were constructed. The AUC of these models was 0.867 and 0.855, respectively. Conclusions : In women with a PCS, measurement of cervical length and head–perineum distance at term is associated with the mode of delivery. A combination of clinical and sonographic parameters at term can predict the likelihood of vaginal delivery.